Neutron-gamma composite shielding material containing lead tungstate filler and preparation method of neutron-gamma composite shielding material
By introducing microspindles, microspheric balls or microsubunctile structures with high specific surface area lead tungstate fillers and boron carbide with high specific surface area in neutron gamma composite shielding materials, combined with high-density polyvinyl matrix, traditional materials are solved for high-energy neutrons and The problem of insufficient gamma ray shielding performance has achieved efficient radiation protection and improved mechanical performance.
Patent Information
- Application Number
- CN202411371781.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-17
AI Technical Summary
Traditional radiation shielding materials show insufficient shielding performance when facing high-energy neutrons and gamma rays, especially the shielding effect of gamma rays is poor, and their microscopic morphology and the radiation, thermal and mechanical properties of composite materials. There are few researches on the correlation mechanism between them, which is difficult to meet the needs of modern applications.
Using micro-spindles, micro-balls or micro-branched structures with high specific surface area lead tungstate filler and boron carbide, combined with high-density polyethylene as the matrix material, neutron gamma composite shielding materials are prepared through hot pressing technology to improve the The material has a neutron and gamma ray shielding capability, and improves the dispersion and interface compatibility of functional fillers in the matrix through high-energy ball milling.
It significantly improves the shielding ability of neutron gamma composite shielding material, enhances its absorption capacity of neutron and gamma rays, and improves the mechanical properties and heat resistance of the material. It is suitable for high-performance radiation in medium and low temperature environments. Protection.
Smart Images

Figure CN119144071A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of radiation protection, and in particular relates to a neutron gamma composite shielding material containing lead tungstate filler and a preparation method thereof. Background Art
[0002] With the advancement of science and technology and industrialization, nuclear technology is increasingly being used in energy, medicine, scientific research, aerospace and other fields. However, when nuclear energy technology is applied, it will produce highly penetrating high-energy neutrons and gamma rays, which will damage human cells and harm human health. Long-term exposure to radiation will lead to gene mutations, cancer and even death. Therefore, it is particularly important to develop efficient radiation shielding materials.
[0003] Traditional radiation shielding materials include concrete and polyethylene. Concrete is heavy, large, and will crack due to aging during long-term use, which limits its application. Polyethylene has low density and single shielding performance. It only has a certain shielding effect on neutrons, and its shielding performance for high-energy gamma rays is poor. It can be seen that the performance of traditional single-component materials is difficult to meet the requirements of the application development of radiation shielding materials. Materials with high atomic numbers and high neutron absorption cross-sections have good shielding effects on gamma rays and neutron radiation, respectively. Adding them as fillers to the matrix material can significantly improve the radiation shielding performance of the material.
[0004] Lead tungstate, as a material with a high atomic number, has good shielding properties against gamma rays. At the same time, lead (Pb) and tungsten (W) have high fast neutron absorption cross sections and can effectively shield fast neutrons, so they are suitable as dual-function absorbers for neutrons and gamma rays. However, most of the current research reports on radiation shielding composite materials are about the optimization of the components of commercial fillers, and there are few reports on the relationship between the micromorphology of fillers and the radiation shielding, thermal and mechanical properties of composite materials. Therefore, it is necessary to synthesize lead tungstate fillers with specific micromorphology and high specific surface area, such as lead tungstate fillers with micron spindle and micron sphere structures, for the research and development of neutron gamma composite shielding materials. Summary of the invention
[0005] In order to solve the shortcomings and deficiencies of polymer-based composite shielding materials, the present invention aims to provide a neutron gamma composite shielding material containing lead tungstate filler and a preparation method thereof. The above-mentioned neutron gamma composite shielding material introduces two types of fillers, namely, lead tungstate (PbWO4) filler with a high specific surface area, micron spindle, micron sphere or micron dendrite structure, and boron carbide (B4C); the introduction of lead tungstate filler with a high specific surface area, micron spindle, micron sphere or micron dendrite structure can increase the probability of interaction between the shielding material and neutrons and gamma rays, and improve the neutron gamma shielding ability of the composite shielding material.
[0006] The present invention is realized by the following technical scheme: a neutron gamma composite shielding material containing micron spindles, micron balls and lead tungstate fillers with micron branch structures, wherein the lead tungstate with micron spindles, micron balls or micron branch structures is used as a dual-function absorber of fast neutrons and gamma rays, boron carbide is used as a thermal neutron absorber, and high-density polyethylene is used as a matrix material. Based on the total mass of the neutron gamma composite shielding material, the mass content of each component of the neutron gamma composite shielding material is as follows: high-density polyethylene: 40-90wt%; boron carbide: 5-40wt%; lead tungstate fillers with micron spindles, micron balls or micron branch structures: 4-50wt%; the density of the high-density polyethylene is 0.90g / cm 3 ~0.99g / cm 3 For example, based on the total mass of the neutron gamma composite shielding material, the mass content of each component of the neutron gamma composite shielding material is: high-density polyethylene: 40wt%, 42wt%, 45wt%, 47wt%, 50wt%, 52wt%, 55wt%, 57wt%, 60wt%, 62wt%, 65wt%, 67wt%, 70wt%, 72wt%, 75wt%, 77wt%, 80wt%, 82wt%, 85wt%, 87wt% or 90wt%;
[0007] Boron carbide: 5wt%, 7wt%, 10wt%, 12wt%, 15wt%, 17wt%, 20wt%, 22wt%, 25wt%, 27wt%, 30wt%, 32wt%, 35wt%, 37wt% or 40wt%;
[0008] Lead tungstate filler with micron spindle, micron ball or micron dendrite structure: 4wt%, 6wt%, 8wt%, 10wt%, 12wt%, 14wt%, 16wt%, 18wt%, 20wt%, 22wt%, 25wt%, 27wt%, 30wt%, 32 wt%, 35wt%, 37wt%, 40wt%, 42wt%, 45wt%, 47wt% or 50wt%.
[0009] Furthermore, the particle size of the lead tungstate filler of the micron spindle, micron ball or micron dendrite structure is 0.005-12 μm, and the specific surface area is 0.1-100 m 2 / g, pore volume is 0.0005~0.5cm 3 / g, and the average pore diameter is 1~150nm. For example, the particle size of the lead tungstate filler of the micron spindle, micron ball or micron dendrite structure is 0.005 μm, 0.006 μm, 0.007 μm, 0.008 μm, 0.009 μm, 0.01 μm, 0.02 μm, 0.03 μm, 0.04 μm, 0.05 μm, 0.06 μm, 0.07 μm, 0.08 μm, 0.09 μm, 0.1 μm, 0.2 μm, 0.4 μm, 0.6 μm, 0.8 μm, 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2 μm, 2.2 μm, 2.4 μm, 2.6 μm, 2.8 μm, 3 μm, 3.2 μm, 3.4 μm, 3.6 μm, 3.8 μm m, 4μm, 4.2μm, 4.4μm, 4.6μm, 4.8μm, 5μm, 5.2μm, 5.4μm, 5.6μm, 5.8μm, 6μm, 6.2μm, 6.4μm, 6.6μm, 6.8μm, 7μm, 7.2μm, 7.4μm, 7.6μm, 7.8μm, 8μm, 8.2μm, 8 .4μm, 8.6μm, 8.8μm, 9μm, 9.2μm, 9.4μm, 9.6μm, 9.8μm, 10μm, 10.2μm, 10.4μm, 10.6μm, 10.8μm, 11μm, 11.2μm, 11.4μm, 11.6μm, 11.8μm or 12μm, with a specific surface area of 0.1m 2 / g, 5m 2 / g, 10m 2 / g, 15m 2 / g, 20m 2 / g, 25m 2 / g, 30m 2 / g, 35m 2 / g, 40m 2 / g, 45m 2 / g, 50m 2 / g, 55m 2 / g, 60m 2 / g, 65m 2 / g, 70m 2 / g, 75m 2 / g, 80m 2 / g, 85m 2 / g, 90m 2 / g, 95m 2 / g or 100m 2 / g, pore volume 0.0005cm 3 / g, 0.001cm 3 / g, 0.002cm 3 / g, 0.003cm3 / g, 0.004cm 3 / g, 0.005cm 3 / g, 0.006cm 3 / g, 0.007cm 3 / g, 0.008cm 3 / g, 0.009cm 3 / g, 0.01cm 3 / g, 0.03cm 3 / g, 0.05cm 3 / g, 0.07cm 3 / g, 0.09cm 3 / g, 0.11cm 3 / g, 0.13cm 3 / g, 0.15cm 3 / g, 0.17cm 3 / g, 0.19cm 3 / g, 0.21cm 3 / g, 0.23cm 3 / g, 0.25cm 3 / g, 0.27cm 3 / g, 0.29cm 3 / g, 0.31cm 3 / g, 0.33cm 3 / g, 0.35cm 3 / g, 0.37cm 3 / g, 0.39cm 3 / g, 0.41cm 3 / g, 0.43cm 3 / g, 0.45cm 3 / g, 0.47cm 3 / g, 0.49cm 3 / g or 0.5cm 3 / g, the average pore diameter is 1nm, 3nm, 5nm, 7nm, 9nm, 11nm, 13nm, 15nm, 17nm, 19nm, 21nm, 23nm, 25nm, 27nm, 29nm, 31nm, 33nm, 35nm, 37nm, 39nm, 41nm, 43nm, 45nm, 47nm, 49nm, 51nm, 53nm, 55nm, 57nm, 59nm, 61nm, 63nm, 65nm, 67nm, 69nm, 71nm, 73nm, 75nm, 77nm, 79nm, 81nm, 83nm, 85nm, 87nm, 89nm, 91nm, 93nm, 95nm, 97nm, 99nm 140nm, 142nm, 144nm, 146nm, 148nm or 150nm.
[0010] A method for preparing a neutron gamma composite shielding material as described above, comprising the following steps: mixing lead tungstate filler, boron carbide and high-density polyethylene with micron spindles, micron balls or micron dendrite structures by ball milling for 1 to 360 minutes to ensure uniform mixing; then placing the mixed powder into a hot press mold, and performing hot pressing operation using a hot press, wherein the hot pressing conditions are: first, keeping warm and pressing for 1 to 30 minutes at 140°C to 400°C and a pressure of 0 to 20 MPa applied to the hot press mold by the hot press, then keeping warm and pressing for 1 to 100 minutes at 140°C to 400°C and a pressure of 5 to 90 MPa applied to the hot press mold by the hot press, and finally keeping warm and pressing for 1 to 200 minutes at 140°C to 400°C and a pressure of 20 to 90 MPa applied to the hot press mold by the hot press; then cooling and demoulding to obtain a neutron gamma shielding composite material.
[0011] Further, a method for preparing a neutron gamma composite shielding material as described above comprises the following steps: ball milling and mixing a lead tungstate filler of a micron spindle or a micron ball or a micron dendrite structure, boron carbide and a high-density polyethylene for 1 min, 5 min, 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, 65 min, 70 min, 75 min, 80 min, 85 min, 90 min, 95 min, 100 min, 105 min, 110 min, 115 min, 120 min, 125 min, 130 min, 135 min, 140 min, 145 min, 150 min, 155 min, 160 min, 165 min, 170 min, 175 min, 180 min, 185 min, 190 min, 191 min, 192 min, 193 min, 194 min, 195 min, 196 min, 197 min, 198 min, 201 min, 202 min, 203 min, 204 min, 205 min, 206 min, 207 min, 208 min, 209 min, 210 min, 211 min, 212 min, 213 min, 214 min, 215 min, 216 min, 217 min, 218 min, 219 min, 220 min, 221 min, 227 min, 228 min, 229 min, 230 min, 231 min, 232 min, 233 min, 234 min, 235 min, min, 195min, 200min, 205min, 210min, 215min, 220min, 225min, 230min, 235min, 240min, 245 min, 250min, 255min, 260min, 265min, 270min, 275min, 280min, 285min, 290min, 295min, 300min, 305min, 310min, 315min, 320min, The mixed powder was then placed in a hot press mold and hot pressed under the following conditions: first at 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 2 Keep the temperature and pressure for 1 to 30 minutes at 30°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C or 400°C, and the pressure applied by the hot press to the hot press mold is 0MPa, 5MPa, 10MPa, 15MPa or 20MPa;The hot press is then heated to 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C or 400°C, and the pressure applied by the hot press to the hot press mold is 5 MPa, 10 MPa, 15 MPa, 20 MPa, 25 MPa, 30 MPa, 35 MPa, 40 MPa, 45 MPa, 50 MPa, 55 MPa, 60 MPa, 65 MPa, 70 MPa, 75 MPa, 80 MPa, 85 MPa or 90 MPa. MPa, keep warm and pressurize for 1min, 5min, 10min, 15min, 20min, 25min, 30min, 35min, 40min, 45min, 50min, 55min, 60 min, 65 min, 70 min, 75 min, 80 min, 85 min, 90min, 95min or 100min; finally, heat and pressurize at 140℃, 150℃, 160℃, 170℃, 180℃, 190℃, 200℃, 210℃, 220℃, 230℃, 240℃, 250℃, 260℃, 270℃, 280℃, 290℃, 300℃, 310℃, 320℃, 330℃, 340℃, 350℃, 360℃, The temperature is 370°C, 380°C, 390°C or 400°C, and the pressure applied by the hot press to the hot press mold is 20MPa, 25MPa, 30MPa, 35MPa, 40MPa, 45MPa, 50MPa, 55MPa, 60MPa, 65MPa, 70MPa, 75MPa, 80MPa, 85MPa or 90MPa, and the temperature and pressure are maintained for 1min, 5min, 10min, 15min, 20min, 25min, 30min, 35min, 40min, 45min, 50min, 55min, 60min, 65min, 70min, 75min, 80min, 85min, 90min, 95min, 100min, 150min or 200min; then cooling and demoulding to obtain a neutron gamma shielding composite material. ;
[0012] Furthermore, the lead tungstate filler with a micron spindle structure is prepared by the following method:
[0013] (1) Weigh sodium tungstate and lead acetate. The molar ratio of sodium tungstate to lead acetate is 0.01~100. For example, the molar ratio of sodium tungstate to lead acetate is 0.01, 0.03, 0.05, 0.07, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.3, 1.5, 1.7, 1.9, 2, 2.1, 2.3, 2.5, 2.7, 2.9, 3, 3.1, 3.3, 3.5, 3.7, 3.9 , 4, 4.1, 4.3, 4.5, 4.7, 4.9, 5, 5.1, 5.3, 5.5, 5.7, 5.9, 6, 6.1, 6.3, 6.5, 6.7, 6.9, 7, 7.1, 7.3, 7.5, 7.7, 7.9, 8, 8.5, 9, 9.5, 10, 20, 30, 40, 50, 60, 70, 80, 90 or 100, respectively, dissolved in ultrapure water;
[0014] (2) Weigh CTAB (cetyltrimethylammonium bromide) and dissolve it in ultrapure water, wherein the concentration of CTAB is 0 M to 10 M; for example, the concentration of CTAB is 0 M, 0.0001 M, 0.0002 M, 0.0003 M, 0.0004 M, 0.0005 M, 0.001 M, 0.002 M, 0.003 M, 0.004 M, 0.005 M, 0.01 M, 0.02 M, 0.03 M, 0.04 M, 0.05 M, 0.1 M, 0.2 M, 0.3 M, 0.4 M, 0.5 M, 1 M, 2 M, 3 M, 4 M, 5 M, 6 M, 7 M, 8 M, 9 M or 10 M;
[0015] (3) Mixing the sodium tungstate and CTAB aqueous solutions, stirring at 10-80°C for 1-120 min to mix the solutions evenly, then gradually adding the lead acetate solution dropwise to the mixed solution, and reacting at 10-80°C for 0.01-12 hours to obtain an emulsion; for example, the mixed solution is reacted at 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C for 0.01 hour, 0.05 hour, 0.1 hour, 0.2 hour, 0.3 hour, 0.4 hour, 0.5 hour, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours or 12 hours;
[0016] (4) centrifuging the emulsion to obtain a precipitate, and washing the precipitate;
[0017] (5) The cleaned precipitated product is placed in an oven and dried at a constant temperature of 30-150°C for 0.1-24 h. For example, the cleaned precipitated product is placed in an oven and dried at a constant temperature of 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, 140, 145 or 150°C for 0.1, 5, 10, 15, 20 or 24 h to obtain the micron spindle structure of lead tungstate.
[0018] Furthermore, the lead tungstate filler with a micron ball structure is prepared by the following method:
[0019] (1) Weigh sodium tungstate and lead acetate. The molar ratio of sodium tungstate to lead acetate is 0.01~100. For example, the molar ratio of sodium tungstate to lead acetate is 0.01, 0.03, 0.05, 0.07, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.3, 1.5, 1.7, 1.9, 2, 2.1, 2.3, 2.5, 2.7, 2.9, 3, 3.1, 3.3, 3.5, 3.7, 3.9, 4, 4.1, 4.3, 4.5, 4.7, 4.9, 5, 5.1, 5.3, 5.5, 5.7, 5.9, 6, 6.1, 6.3, 6.5, 6.7, 6.9, 7, 7.1, 7.3, 7.5, 7.7, 7.9, 8, 8.5, 9, 9.5, 10, 20, 30, 40, 50, 60, 70, 80, 90 or 100, respectively, dissolved in ethylene glycol solution;
[0020] (2) Mix sodium tungstate and lead acetate ethylene glycol solutions and stir for 1-100 min, pour the mixed solution into a reactor, put it in a drying oven and keep it warm at 30℃, 40℃, 50℃, 60℃, 70℃, 80℃, 90℃, 100℃, 110℃, 120℃, 130℃, 140℃, 150℃, 160℃, 170℃, 180℃, 190℃, 200℃, 210℃, 220℃, 230℃, 240℃, or 250℃ for 1 min, 5 min, 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, 65 min, 70 min, 75 min min, 80 min, 85 min, 90 min, 95 min, 100 min, 105 min, 110 min, 115 min or 120 min to obtain an emulsion;
[0021] (3) centrifuging the emulsion to obtain a precipitate, and washing the precipitate;
[0022] (4) The cleaned precipitated product is placed in an oven and dried at a constant temperature of 30-150°C for 0.1-24 h. For example, the cleaned precipitated product is placed in an oven and dried at a constant temperature of 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, 140, 145 or 150°C for 0.1, 5, 10, 15, 20 or 24 h to obtain the lead tungstate with the micron spherical structure.
[0023] Furthermore, the lead tungstate filler having a micron spindle structure without CTAB (0M CTAB) is prepared by the following method:
[0024] (1) Weigh sodium tungstate and lead acetate. The molar ratio of sodium tungstate to lead acetate is 0.01~100. For example, the molar ratio of sodium tungstate to lead acetate is 0.01, 0.03, 0.05, 0.07, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.3, 1.5, 1.7, 1.9, 2, 2.1, 2.3, 2.5, 2.7, 2.9, 3, 3.1, 3.3, 3.5, 3.7, 3.9 , 4, 4.1, 4.3, 4.5, 4.7, 4.9, 5, 5.1, 5.3, 5.5, 5.7, 5.9, 6, 6.1, 6.3, 6.5, 6.7, 6.9, 7, 7.1, 7.3, 7.5, 7.7, 7.9, 8, 8.5, 9, 9.5, 10, 20, 30, 40, 50, 60, 70, 80, 90 or 100, respectively, dissolved in ultrapure water;
[0025] (2) mixing sodium tungstate and lead acetate aqueous solutions, and reacting them at a constant temperature of 10 to 80° C. for 0.01 to 12 hours to obtain an emulsion; for example, the mixed solution is reacted at a constant temperature of 10° C., 15° C., 20° C., 25° C., 30° C., 35° C., 40° C., 45° C., 50° C., 55° C., 60° C., 65° C., 70° C., 75° C., or 80° C. for 0.01 hour, 0.05 hour, 0.1 hour, 0.2 hour, 0.3 hour, 0.4 hour, 0.5 hour, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, or 12 hours;
[0026] (3) centrifuging the emulsion to obtain a precipitate, and washing the precipitate;
[0027] (4) The cleaned precipitated product is placed in an oven and dried at a constant temperature of 30-150°C for 0.1-24 h. For example, the cleaned precipitated product is placed in an oven and dried at a constant temperature of 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C or 150°C for 0.1 h, 5 h, 10 h, 15 h, 20 h or 24 h to obtain the lead tungstate with the micron spindle structure.
[0028] Furthermore, the lead tungstate filler with a micron-dendritic structure is prepared by the following method:
[0029] (1) Weigh sodium tungstate and lead acetate. The molar ratio of sodium tungstate to lead acetate is 0.01~100. For example, the molar ratio of sodium tungstate to lead acetate is 0.01, 0.03, 0.05, 0.07, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.3, 1.5, 1.7, 1.9, 2, 2.1, 2.3, 2.5, 2.7, 2.9, 3, 3.1, 3.3, 3.5, 3.7, 3.9 , 4, 4.1, 4.3, 4.5, 4.7, 4.9, 5, 5.1, 5.3, 5.5, 5.7, 5.9, 6, 6.1, 6.3, 6.5, 6.7, 6.9, 7, 7.1, 7.3, 7.5, 7.7, 7.9, 8, 8.5, 9, 9.5, 10, 20, 30, 40, 50, 60, 70, 80, 90 or 100, respectively, dissolved in ultrapure water;
[0030] (2) mixing sodium tungstate and lead acetate aqueous solutions, and reacting them at a constant temperature of 50 to 100° C. for 0.01 to 12 hours to obtain an emulsion; for example, the mixed solution is reacted at a constant temperature of 50° C., 55° C., 60° C., 65° C., 70° C., 75° C., 80° C., 85° C., 90° C., 95° C. or 100° C. for 0.01 hour, 0.05 hour, 0.1 hour, 0.2 hour, 0.3 hour, 0.4 hour, 0.5 hour, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours or 12 hours;
[0031] (3) centrifuging the emulsion to obtain a precipitate, and washing the precipitate;
[0032] (4) The cleaned precipitated product is placed in an oven and dried at a constant temperature of 30-150°C for 0.1-24h. For example, the cleaned precipitated product is placed in an oven and dried at a constant temperature of 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C or 150°C for 0.1h, 5h, 10h, 15h, 20h or 24h to obtain the micron-dendritic lead tungstate.
[0033] The present invention has the following beneficial effects:
[0034] The neutron gamma composite shielding material is suitable for high-performance neutron gamma radiation shielding in medium and low temperature (not exceeding 100°C) or normal temperature environments, such as nuclear facility radiation protection, space station and spacecraft cabin radiation protection, radiation source library radiation protection, nuclear waste preparation, radiation medical radiation protection, etc. The advantages of the present invention are: two fillers of PbWO4 and B4C with high specific surface area micron spindles or micron balls or micron dendrites are introduced into the neutron gamma composite shielding material; the introduction of PbWO4 fillers with high specific surface area micron spindles or micron balls or micron dendrites can increase the probability of interaction with neutrons and gamma rays, and improve the neutron gamma shielding ability of the composite shielding material; in addition, the neutron absorption energy ranges of PbWO4 and B4C can complement each other, wherein the fast neutron absorption cross section of Pb and W is higher, and the thermal neutron absorption cross section of B4C is higher. In addition, high-energy ball milling and processing are used to improve the dispersion of functional fillers in the matrix, improve the interface compatibility between the functional fillers and the matrix material, and enhance the mechanical properties and heat resistance of the neutron gamma composite shielding material. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 SEM images of micron spindle, micron sphere and micron dendrite structured PbWO4 fillers, (a) 0.001M CTAB micron spindle structured lead tungstate filler (PbWO4-I), (b) 0.05M CTAB micron spindle structured lead tungstate filler (PbWO4-II), (c) 0.3M CTAB micron spindle structured lead tungstate filler (PbWO4-III), (d) micron sphere structured lead tungstate filler (PbWO4-IV), (e) 0M CTAB micron spindle structured lead tungstate filler (PbWO4-V), (f) micron dendrite structured lead tungstate filler prepared from aqueous solution (PbWO4-VI);
[0036] Figure 2 XRD spectra of micron spindle, micron ball and micron dendrite structure lead tungstate fillers;
[0037] Figure 3 N2 adsorption-desorption isotherms (b) and pore size distribution diagram (a) of micron spindle, micron sphere and micron dendrite structure lead tungstate fillers;
[0038] Figure 4 Schematic diagram of neutron and gamma shielding performance test device, (a) Schematic diagram of neutron shielding performance test device, (b) Schematic diagram of gamma shielding performance test device. DETAILED DESCRIPTION
[0039] The protection scope of the present invention shall include all the contents of the claims. The present invention will be described in detail below through specific embodiments. The embodiments are limited to explaining the present invention. In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention will be explained in combination with the drawings and specific embodiments. Through the specific description of the drawings and embodiments, researchers in this field can fully grasp all the contents of the invention claims.
[0040] In the following examples of the present invention, some of the raw materials and testing methods used are as follows:
[0041] High-density polyethylene powder (China Petrochemical Corporation Maoming Branch, product model HHW5502LW, density 0.96g / cm 3 );
[0042] Material characterization test description: SEM image (field emission scanning electron microscope, Carl Zeiss Group, Germany, model ΣIGMA);
[0043] XRD spectrum (X-ray diffractometer, Rigaku Corporation, Japan, model TTR-III);
[0044] BET specific surface area (m 2 / g), pore volume (cm 3 / g) and average pore diameter (nm) data were obtained by testing the specific surface area and porosity analyzer (McMerritt Instruments, Inc., USA, model TristarII3020). The specific process is: the material is placed in a N2 environment, and the N2 isothermal adsorption-desorption curve of the material is obtained by changing the relative pressure of N2. The specific surface area is calculated using the Brunauer-Emmett-Teller (BET) model, and the average pore diameter and pore volume are calculated using the Barret-Joyner-Halenda (BJH) model.
[0045] The mechanical properties test includes two parts: the Shore hardness test and the mechanical tensile test. The Shore hardness test uses the LX-D-2 Shore hardness tester of Dongguan Sanliang Precision Measuring Instrument Co., Ltd. The sample is placed on the horizontal sample table of the hardness tester, and then the steel needle at the indenter is vertically pressed into the sample, vertically fitting with the sample surface, and the reading of the hardness tester is recorded at this time. The experiment is repeated five times in parallel, and the average value is taken to obtain the Shore hardness value of the sample. Parameters such as Young's modulus, yield strength, and elongation at break are obtained through mechanical tensile testing. The mechanical tensile test uses the Instron3367 electronic universal material testing machine of Instron, UK. The prepared tensile sample specification is GBT1040.2-20061BA, and the tensile rate is 5mm / min.
[0046] The neutron shielding performance test device consists of a polyethylene collimating shielding tube, 252 The Cf neutron source and high-sensitivity neutron detector are arranged as follows: Figure 4 As shown in (a), the length of the polyethylene collimation shielding tube is 150 cm, the wall thickness of the polyethylene collimation shielding tube is 33.5 cm, and there is a through hole with a diameter of 5 cm in the middle of the polyethylene collimation shielding tube. The high-sensitivity neutron detector is located 20 cm away from the exit of the polyethylene collimation shielding tube. The specific process of neutron shielding test: First, use a high-sensitivity neutron detector (Fluke Instruments, Inc., USA, model SmartREM) to detect the unloaded 252 Neutron count in the environment with Cf neutron source and shielding material to be tested, marked as In 0b ; Then place the shielding material to be tested close to the exit hole of the polyethylene collimating shielding tube and record the unloaded 252 Cf neutron source, neutron count displayed by the neutron detector when the shielding material to be tested is loaded, marked as In b ; Then remove the shielding material to be tested at the exit hole of the polyethylene collimating shielding tube, and 252 The Cf neutron source is placed in a designated position in the polyethylene collimation shielding tube (30 cm from the exit port), and a high-sensitivity neutron detector is used to detect the neutron count in the current state, marked as In0; then shielding material is placed close to the exit hole of the polyethylene collimation shielding tube, and the loading is recorded. 252 The neutron count displayed by the neutron detector when the neutron source is Cf and the shielding material is tested is marked as In; each set of tests is repeated 10 times and the average value is taken.
[0047] Neutron shielding rate S n The calculation formula is: Sn=(1–In / In0)×100%
[0048] The gamma ray shielding performance test device consists of a lead collimated shielding tube, 137 Cs gamma source and portable radiation detector, the layout is as follows Figure 4As shown in (b), the length of the lead collimation shielding tube is 50 cm, the wall thickness of the lead collimation shielding tube is 16 cm, and there is a through hole with a diameter of 1 cm in the middle of the lead collimation shielding tube. The portable radiation detector is located 20 cm away from the exit of the lead collimation shielding tube. The specific process of gamma ray shielding test: First, a portable radiation detector (Thermo Fisher Scientific, USA, model FHZ672E-10) is used to detect the unloaded 137 Gamma counts in the environment with Cs gamma source and shielding material under test, marked as Iγ 0b ; Then place the shielding material close to the exit hole of the lead collimation shielding tube and record the unloaded 137 Cs gamma source, gamma counts displayed by a portable radiation detector when loaded with shielding material to be tested, labeled Iγ b ; Then remove the shielding material to be tested at the exit hole of the lead collimation shielding tube, and 137 Place the Cs gamma source in the designated position of the lead collimation shielding tube (20 cm from the exit port), use a portable radiation detector to detect the gamma count in the current state, marked as Iγ0; then place shielding material close to the exit hole of the lead collimation shielding tube, and record the placement. 137 The gamma counts displayed by the portable radiation detector when using the Cs gamma source and the shielding material to be tested are marked as Iγ; each set of tests is repeated 10 times and the average value is taken.
[0049] Gamma shielding rate S γ The calculation formula is: γ =(1-I γ / I γ0 )×100%
[0050] Example 1
[0051] Use an electronic analytical balance to weigh 0.01 mol sodium tungstate and 0.01 mol lead acetate powder respectively, dissolve them in 50 ml ultrapure water, and stir the solution at room temperature for 30 minutes to make it completely dissolved. Then weigh 0.01 mol CTAB and dissolve it in 100 ml ultrapure water, mix and stir the sodium tungstate solution and CTAB solution for 30 minutes, place the beaker of the mixed solution in an oil bath, keep it warm at 28°C, add the lead acetate solution drop by drop into the mixed solution of sodium tungstate and CTAB, keep the temperature of the reactant solution at 28°C, and the reaction time is 30 minutes. After the reaction is completed, the emulsion solution in the beaker is transferred into a centrifuge tube, and the centrifuge tube is placed in a centrifuge and centrifuged at 8000r / min for about 4 minutes. After the centrifugation is completed, the supernatant in the centrifuge tube is poured out, and ultrapure water is added to the centrifuge tube to continue centrifugation. The above operation is repeated 5 times until the supernatant is clear; then ethanol is added to the centrifuge tube and the centrifugation operation is continued. After each centrifugation, the supernatant in the centrifuge tube is poured out, and ethanol is added to the centrifuge tube to continue centrifugation. Repeat the above process 5 times until the supernatant is clear, indicating that the impurities in the precipitate in the centrifuge tube are completely removed. The precipitate in the centrifuge tube is then placed in an oven and dried at 60°C for 6 hours to obtain PbWO4 with a micron spindle structure, which is marked as micron spindle PbWO4-I (0.001MCTAB). The SEM image, XRD spectrum, N2 adsorption and desorption isotherm and pore size distribution diagram and BET specific surface area parameters of micron spindle PbWO4-I are shown as follows: Figure 1 (a) Figure 2 , Figure 3 As shown in (a) and Table 1, the XRD spectrum shows that PbWO4-I belongs to the tetragonal system, body-centered lattice, and space group is I41 / a (88); SEM images and BET tests show that the morphology of PbWO4-I is partly nanoscale particles, as well as pyramidal and smaller micron spindle particles. The particle size is mostly around 0.1-3μm, and its BET specific surface area is 0.64m 2 / g. 72g of PbWO4-I powder, 36g of B4C powder and 252g of high-density polyethylene powder were weighed respectively, and the three powders were put into a high-energy ball mill and mixed at 800rpm / min for 15min, and the mixed powder was put into a hot press mold and a demoulding paper was put into the hot press, and the hot press was used for hot pressing. The hot pressing conditions were: first, pre-pressing at 160℃ and 2MPa (the pressure applied by the hot press to the hot press mold, the same as in the following embodiments) for 10min, then keeping warm and pressing at 160℃ and 30MPa (the pressure applied by the hot press to the hot press mold, the same as in the following embodiments) for 30min, and finally keeping warm and pressing at 160℃ and 55MPa (the pressure applied by the hot press to the hot press mold, the same as in the following embodiments) for 60min; then, after cooling to room temperature, the pressure was released and demoulding was performed to obtain the PbWO4-I / B4C / HDPE neutron gamma shielding composite material.
[0052] The heat resistance and mechanical properties of the composite material prepared in this embodiment are shown in Table 2 and Table 3. The neutron shielding performance test device consists of a polyethylene collimating shielding tube, 252 The Cf neutron source and high-sensitivity neutron detector are composed of a neutron shielding rate of 42.02% when the material thickness is 1.5 cm; the gamma-ray shielding performance test device consists of a lead collimated shielding tube, 137 Cs gamma source and portable radiation detector. When the material thickness is 1.5cm, the gamma ray shielding rate is 12.48%.
[0053] Example 2
[0054] Use an electronic analytical balance to weigh 0.01 mol sodium tungstate and 0.01 mol lead acetate powder respectively, dissolve them in 50 ml ultrapure water, and stir the solution at room temperature for 30 minutes to make it completely dissolved. Then weigh 0.5 mol CTAB and dissolve it in 100 ml ultrapure water, mix and stir the sodium tungstate solution and CTAB solution for 30 minutes, place the beaker of the mixed solution in an oil bath, keep it warm at 28°C, add the lead acetate solution drop by drop into the mixed solution of sodium tungstate and CTAB, keep the temperature of the reactant solution at 28°C, and the reaction time is 30 minutes. After the reaction is completed, the emulsion solution in the beaker is transferred into a centrifuge tube, and the centrifuge tube is placed in a centrifuge and centrifuged at 8000r / min for about 4 minutes. After the centrifugation is completed, the supernatant in the centrifuge tube is poured out, and ultrapure water is added to the centrifuge tube to continue centrifugation. The above operation is repeated 5 times until the supernatant is clear; then ethanol is added to the centrifuge tube and the centrifugation operation is continued. After each centrifugation, the supernatant in the centrifuge tube is poured out, and ethanol is added to the centrifuge tube to continue centrifugation. Repeat the above process 5 times until the supernatant is clear, indicating that the impurities in the precipitate in the centrifuge tube are completely removed. The precipitate in the centrifuge tube is then placed in an oven and dried at 60°C for 6 hours to obtain PbWO4 with a micron spindle structure, which is marked as micron spindle PbWO4-II (0.05MCTAB). The SEM image, XRD spectrum, N2 adsorption and desorption isotherm and pore size distribution diagram and BET specific surface area parameters of micron spindle PbWO4-II are shown as follows: Figure 1 (b) Figure 2 , Figure 3 As shown in (a) and Table 1, the XRD spectrum shows that PbWO4-II belongs to the tetragonal system, body-centered lattice, and space group is I41 / a(88); SEM images and BET tests show that the morphology of PbWO4-II is partly nanoscale particles, as well as pyramidal and smaller micron spindle particles. The particle size is mostly around 3-5 μm, and its BET specific surface area is 1.02 m 2 / g. 72g of PbWO4-II powder, 36g of B4C powder and 252g of high-density polyethylene powder were weighed respectively, and the three powders were put into a high-energy ball mill for ball milling and mixing at 800rpm / min for 15min. The mixed powder was put into a hot press mold and a demoulding paper was put in. The hot press was used for hot pressing. The hot pressing conditions were: first, pre-pressing at 160℃ and 2MPa for 10min, then keeping the temperature and pressure at 160℃ and 30MPa for 30min, and finally keeping the temperature and pressure at 160℃ and 55MPa for 60min; then, the PbWO4-II / B4C / HDPE neutron gamma shielding composite material was obtained after cooling to room temperature, pressure relief and demoulding.
[0055] The heat resistance and mechanical properties of the composite material prepared in this embodiment are shown in Table 2 and Table 3. The neutron shielding performance test device consists of a polyethylene collimating shielding tube, 252 The neutron source and high-sensitivity neutron detector are composed of a Cf neutron source and a high-sensitivity neutron detector. When the material thickness is 1.5 cm, the neutron shielding rate is 42.56%; the gamma-ray shielding performance test device consists of a lead collimated shielding tube, 137 Cs gamma source and portable radiation detector. When the material thickness is 1.5cm, the gamma ray shielding rate is 12.98%.
[0056] Example 3
[0057] Use an electronic analytical balance to weigh 0.01 mol of sodium tungstate and 0.01 mol of lead acetate powder, respectively, and dissolve them in 50 ml of ultrapure water. Stir the solution at room temperature for 30 minutes to completely dissolve it. Then weigh 3 mol of CTAB and dissolve it in 100 ml of ultrapure water. Mix and stir the sodium tungstate solution and CTAB solution for 30 minutes. Place the beaker of the mixed solution in an oil bath pot and keep it warm at 28°C. Add the lead acetate solution drop by drop into the mixed solution of sodium tungstate and CTAB. Keep the temperature of the reactant solution at 28°C and the reaction time for 30 minutes. After the reaction is completed, the emulsion solution in the beaker is transferred into a centrifuge tube, and the centrifuge tube is placed in a centrifuge and centrifuged at 8000r / min for about 4 minutes. After the centrifugation is completed, the supernatant in the centrifuge tube is poured out, and ultrapure water is added to the centrifuge tube to continue centrifugation. The above operation is repeated 5 times until the supernatant is clear; then ethanol is added to the centrifuge tube and the centrifugation operation is continued. After each centrifugation, the supernatant in the centrifuge tube is poured out, and ethanol is added to the centrifuge tube to continue centrifugation. Repeat the above process 5 times until the supernatant is clear, indicating that the impurities in the precipitate in the centrifuge tube are completely removed. The precipitate in the centrifuge tube is then placed in an oven and dried at 60°C for 6 hours to obtain PbWO4 with a micron spindle structure, which is marked as micron spindle PbWO4-III (0.3MCTAB). The SEM image, XRD spectrum, N2 adsorption and desorption isotherm and pore size distribution diagram and BET specific surface area parameters of micron spindle PbWO4-III are shown as follows: Figure 1 (c) Figure 2 , Figure 3 As shown in (a) and Table 1, the XRD spectrum shows that PbWO4-III belongs to the tetragonal system, body-centered lattice, and space group is I41 / a(88); SEM images and BET tests show that the morphology of PbWO4-III is partly nanoscale particles, as well as pyramidal and smaller micron spindle particles, and the particle size is mostly around 5-8 μm, and its BET specific surface area is 1.76 m 2 / g. 72g of PbWO4-III powder, 36g of B4C powder and 252g of high-density polyethylene powder were weighed respectively, and the three powders were put into a high-energy ball mill for ball milling and mixing at 800rpm / min for 15min. The mixed powder was put into a hot press mold and a demoulding paper was put in. The hot press was used for hot pressing. The hot pressing conditions were: first, pre-pressing at 160℃ and 2MPa for 10min, then keeping the temperature and pressure at 160℃ and 30MPa for 30min, and finally keeping the temperature and pressure at 160℃ and 55MPa for 60min; then, the PbWO4-III / B4C / HDPE neutron gamma shielding composite material was obtained after cooling to room temperature, pressure relief and demoulding.
[0058] The heat resistance and mechanical properties of the composite material prepared in this embodiment are shown in Table 2 and Table 3. The neutron shielding performance test device consists of a polyethylene collimating shielding tube, 252 The neutron source and high-sensitivity neutron detector are composed of a Cf neutron source and a high-sensitivity neutron detector. When the material thickness is 1.5 cm, the neutron shielding rate is 44.26%; the gamma-ray shielding performance test device consists of a lead collimated shielding tube, 137 Cs gamma source and portable radiation detector. When the material thickness is 1.5cm, the gamma ray shielding rate is 13.75%.
[0059] Example 4
[0060] Use an electronic analytical balance to weigh 0.004mol sodium tungstate and 0.004mol lead acetate powder respectively, dissolve them in 50ml ethylene glycol respectively, and stir the solution at room temperature for 60min to completely dissolve them. Then mix and stir the sodium tungstate ethylene glycol solution and the lead acetate ethylene glycol solution for 5min, pour the mixed solution into the reactor, place it in a constant temperature drying oven and keep it at 160℃ for 2h, after the reaction is completed, wait for the reactor to cool to room temperature, transfer the emulsion in the reactor into a centrifuge tube, put the centrifuge tube into a centrifuge and centrifuge it at 8000r / min for about 4min, pour out the supernatant in the centrifuge tube after the centrifugation is completed, add ultrapure water to the centrifuge tube and continue centrifugation, repeat the above operation 5 times until the supernatant is clear; then add ethanol to the centrifuge tube and continue centrifugation, pour out the supernatant in the centrifuge tube after each centrifugation, add ethanol to the centrifuge tube and continue centrifugation, repeat the above process 5 times until the supernatant is clear, indicating that the impurities in the sediment in the centrifuge tube are completely removed. Then, the precipitate in the centrifuge tube was placed in an oven and dried at 60°C for 6 hours to obtain PbWO4 with a micron-sphere structure, which was labeled as micron-sphere PbWO4-IV. The SEM image, XRD spectrum, N2 adsorption-desorption isotherm, pore size distribution and BET specific surface area parameters of micron-sphere PbWO4-IV are shown in Figure 2. Figure 1 (d) Figure 2 , Figure 3(b) and Table 1, the XRD spectrum shows that PbWO4-IV belongs to the tetragonal system, body-centered lattice, and space group is I41 / a(88); SEM images and BET tests show that the morphology of PbWO4-IV is micron-spherical particles with a size of 2-3 μm, and its BET-specific surface area is 6.19 m 2 / g. 72g PbWO4-IV powder, 36g B4C powder and 252g high-density polyethylene powder were weighed respectively, and the three powders were put into a high-energy ball mill and mixed at 800rpm / min for 15min. The mixed powder was put into a hot press mold and a demoulding paper was put in. The hot press was used for hot pressing. The hot pressing conditions were: first pre-pressing at 160℃ and 2MPa for 10min, then keeping the temperature and pressure at 160℃ and 30MPa for 30min, and finally keeping the temperature and pressure at 160℃ and 55MPa for 60min; then cooling to room temperature, releasing the pressure and demoulding were performed to obtain the PbWO4-IV / B4C / HDPE neutron gamma shielding composite material.
[0061] The heat resistance and mechanical properties of the composite material prepared in this embodiment are shown in Table 2 and Table 3. The neutron shielding performance test device consists of a polyethylene collimating shielding tube, 252 The Cf neutron source and high-sensitivity neutron detector are composed of a neutron shielding rate of 46.48% when the material thickness is 1.5 cm; the gamma-ray shielding performance test device consists of a lead collimated shielding tube, 137 Cs gamma source and portable radiation detector. When the material thickness is 1.5cm, the gamma ray shielding rate is 14.49%.
[0062] Example 5
[0063] Use an electronic analytical balance to weigh 0.01mol sodium tungstate and 0.01mol lead acetate powder respectively, dissolve them in 50ml ultrapure water respectively, and stir the solution at room temperature for 30min to completely dissolve them. Mix and stir the sodium tungstate solution and the lead acetate solution, keep the temperature of the mixed solution at 28℃, and the reaction time is 60min. After the reaction is completed, transfer the emulsion solution in the beaker into a centrifuge tube, put the centrifuge tube into a centrifuge and centrifuge it at 8000r / min for about 4min. After the centrifugation is completed, pour out the supernatant in the centrifuge tube, add ultrapure water to the centrifuge tube and continue centrifugation. Repeat the above operation 5 times until the supernatant is clear; then add ethanol to the centrifuge tube and continue centrifugation. After each centrifugation, pour out the supernatant in the centrifuge tube, add ethanol to the centrifuge tube and continue centrifugation. Repeat the above process 5 times until the supernatant is clear, indicating that the impurities in the sediment in the centrifuge tube are completely removed. Then, the precipitate in the centrifuge tube was placed in an oven and dried at 60°C for 6 h to obtain PbWO4 with a micron spindle structure, which was labeled as micron spindle PbWO4-V. The SEM image, XRD spectrum, N2 adsorption-desorption isotherm, pore size distribution and BET specific surface area parameters of micron spindle PbWO4-V are shown in Figure 2. Figure 1 (e) Figure 2 , Figure 3 (b) and Table 1, the XRD spectrum shows that PbWO4-V belongs to the tetragonal system, body-centered lattice, and the space group is I41 / a (88); SEM images and BET tests show that the morphology of PbWO4-V is micron spindle-shaped particles with a size of 6-12 μm, and its BET-specific surface area is 0.63 m 2 / g. 72g PbWO4-V powder, 36g B4C powder and 252g high-density polyethylene powder were weighed respectively, and the three powders were put into a high-energy ball mill for ball milling and mixing at 800rpm / min for 15min. The mixed powder was put into a hot press mold and a demoulding paper was put in. The hot press was used for hot pressing. The hot pressing conditions were: first pre-pressing at 160℃ and 2MPa for 10min, then keeping warm and pressing at 160℃ and 30MPa for 30min, and finally keeping warm and pressing at 160℃ and 55MPa for 60min; then cooling to room temperature, releasing pressure and demoulding were performed to obtain the PbWO4-V / B4C / HDPE neutron gamma shielding composite material.
[0064] The heat resistance and mechanical properties of the composite material prepared in this embodiment are shown in Table 2 and Table 3. The neutron shielding performance test device consists of a polyethylene collimating shielding tube, 252 The Cf neutron source and high-sensitivity neutron detector are composed of a neutron shielding rate of 43.7% when the material thickness is 1.5 cm; the gamma-ray shielding performance test device consists of a lead collimated shielding tube, 137Cs gamma source and portable radiation detector. When the material thickness is 1.5cm, the gamma ray shielding rate is 12.28%.
[0065] Example 6
[0066] Use an electronic analytical balance to weigh 0.01mol sodium tungstate and 0.01mol lead acetate powder respectively, dissolve them in 50ml ultrapure water respectively, and stir the solution at room temperature for 30min to completely dissolve them. Mix and stir the sodium tungstate solution and the lead acetate solution, keep the temperature of the mixed solution at 90℃, and the reaction time is 2h. After the reaction is completed, transfer the emulsion solution in the beaker into a centrifuge tube, put the centrifuge tube into a centrifuge and centrifuge it at 8000r / min for about 4min. After the centrifugation is completed, pour out the supernatant in the centrifuge tube, add ultrapure water to the centrifuge tube and continue centrifugation. Repeat the above operation 5 times until the supernatant is clear; then add ethanol to the centrifuge tube and continue centrifugation. After each centrifugation, pour out the supernatant in the centrifuge tube, add ethanol to the centrifuge tube and continue centrifugation. Repeat the above process 5 times until the supernatant is clear, indicating that the impurities in the sediment in the centrifuge tube are completely removed. Then, the precipitate in the centrifuge tube was placed in an oven and dried at 60°C for 6 hours to obtain PbWO4 with a micron-dendritic structure, which was labeled as micron-dendritic PbWO4-VI. The SEM image, XRD spectrum, N2 adsorption-desorption isotherm, pore size distribution and BET specific surface area parameters of micron-dendritic PbWO4-VI are shown in Figure 2. Figure 1 (f) Figure 2 , Figure 3 (b) and Table 1, the XRD spectrum shows that PbWO4-VI belongs to the tetragonal system, body-centered lattice, and the space group is I41 / a (88); SEM images and BET tests show that the morphology of PbWO4-VI is micron dendrite particles with a size of 6-12 μm, and its BET-specific surface area is 0.88 m 2 / g. 72g of PbWO4-VI powder, 36g of B4C powder and 252g of high-density polyethylene powder were weighed respectively, and the three powders were put into a high-energy ball mill for ball milling and mixing at 800rpm / min for 15min. The mixed powder was put into a hot press mold and a demoulding paper was put in. The hot press was used for hot pressing. The hot pressing conditions were: first, pre-pressing at 160℃ and 2MPa for 10min, then keeping warm and pressing at 160℃ and 30MPa for 30min, and finally keeping warm and pressing at 160℃ and 55MPa for 60min; then, the PbWO4-VI / B4C / HDPE neutron gamma shielding composite material was obtained after cooling to room temperature, pressure relief and demoulding.
[0067] The heat resistance and mechanical properties of the composite material prepared in this embodiment are shown in Table 2 and Table 3. The neutron shielding performance test device consists of a polyethylene collimating shielding tube,252 The Cf neutron source and high-sensitivity neutron detector are composed of a neutron shielding rate of 44.32% when the material thickness is 1.5 cm; the gamma-ray shielding performance test device consists of a lead collimated shielding tube, 137 Cs gamma source and portable radiation detector. When the material thickness is 1.5cm, the gamma ray shielding rate is 12.2%.
[0068] Table 1 BET specific surface area and other parameters of micron spindle, micron ball and micron dendrite structure PbWO4 filler
[0069]
[0070] Table 2 Thermal stability parameters of neutron gamma composite shielding materials containing micron spindles, micron balls and micron dendrite structure PbWO4 fillers
[0071]
[0072] Table 3 Mechanical properties of neutron gamma composite shielding materials containing micron spindles, micron balls and micron dendrite structure PbWO4 fillers
[0073]
[0074] The present invention does not elaborate on some of the common technologies of those skilled in the art. The above-described embodiments are only descriptions of preferred implementations of the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementations described. Without departing from the design spirit of the present invention, various modifications and improvements made by ordinary technicians in this field to the technical solution of the present invention should fall within the scope of protection determined by the claims of the present invention.
Claims
1. A neutron gamma composite shielding material filled with lead tungstate, characterized in that: The invention adopts a lead tungstate filler with a controllable micron spindle, micron ball or micron branch structure as a dual-function absorber of fast neutrons and gamma rays, boron carbide as a thermal neutron absorber, and high-density polyethylene as a matrix material. The mass content of each component of the neutron gamma composite shielding material is as follows: high-density polyethylene: 40-90wt%, boron carbide: 5-40wt%, lead tungstate filler with a controllable micron spindle, micron ball or micron branch structure: 4-50wt%; the density of the high-density polyethylene is 0.90g / cm 3 ~0.99g / cm 3 .
2. The neutron gamma composite shielding material according to claim 1, characterized in that: The lead tungstate filler with controllable micron spindle, micron ball or micron dendrite structure has a particle size of 0.01-12 μm and a specific surface area of 0.1-100 m 2 / g, pore volume is 0.0005~0.5cm 3 / g, and the average pore diameter is 1~150nm.
3. A method for preparing the neutron gamma composite shielding material according to claim 1, characterized in that: The following steps are involved: The lead tungstate filler with a controllable morphology of micron spindles, micron balls or micron dendrites, boron carbide and high-density polyethylene are mixed and ball-milled for 1-360 minutes to ensure uniform mixing; the mixed particles are placed in a hot press mold, and a hot press is used for hot pressing, and the hot pressing conditions are: first, the temperature is kept at 140°C-400°C and the pressure applied by the hot press to the hot press mold is 0-20MPa for 1-30 minutes, then the temperature is kept at 140°C-400°C and the pressure applied by the hot press to the hot press mold is 5-90MPa for 10-100 minutes, and finally, the temperature is kept at 140°C-400°C and the pressure applied by the hot press to the hot press mold is 20-90MPa for 10-200 minutes; Then the mold is released by cooling and depressurization to obtain the neutron gamma composite shielding material.
4. The preparation method according to claim 3, characterized in that: The lead tungstate filler with controllable morphology micron spindle structure is prepared by the following method: (1) weighing sodium tungstate and lead acetate, the molar ratio of sodium tungstate to lead acetate is 0.01-100, and dissolving them in ultrapure water respectively; (2) weighing CTAB (cetyltrimethylammonium bromide) and dissolving it in ultrapure water, the concentration of CTAB is 0M-10M; (3) mixing the sodium tungstate and CTAB aqueous solutions, stirring at 10-80°C for 1-120min to make the solutions evenly mixed, then gradually adding the lead acetate solution dropwise to the mixed solution, reacting at a constant temperature of 10-80°C for 0.01-12 hours to obtain an emulsion; (4) centrifuging the emulsion to obtain a precipitate, and washing the precipitate; (5) placing the washed precipitate product in an oven and drying it at a constant temperature of 30-150°C for 0.1-24h to obtain the lead tungstate with the micron spindle structure.
5. The preparation method according to claim 3, characterized in that: The lead tungstate filler with controllable morphology and micron-spherical structure is prepared by the following method: (1) sodium tungstate and lead acetate are weighed, the molar ratio of sodium tungstate to lead acetate is 0.01-100, and the two are dissolved in ethylene glycol solution respectively; (2) the sodium tungstate solution and the lead acetate solution are mixed and stirred for 1-100 minutes, and then the mixed solution is poured into a reaction kettle, and placed in a drying oven for insulation at 30°C-250°C for reaction for 1-120 minutes; (3) the emulsion is centrifuged to obtain a precipitate, and the precipitate is washed; (4) the washed precipitate product is placed in an oven and dried at a constant temperature of 30-150°C for 0.1-24 hours to obtain the lead tungstate with micron-spherical structure.
6. The preparation method according to claim 3, characterized in that: The lead tungstate filler with a controllable micron-branched structure is prepared by the following method: (1) weighing sodium tungstate and lead acetate, wherein the molar ratio of sodium tungstate to lead acetate is 0.01-100, and dissolving them in an ultrapure aqueous solution respectively; (2) mixing the sodium tungstate solution and the lead acetate solution, and reacting them at a constant temperature of 50-100° C. for 0.01-12 hours to obtain an emulsion; (3) centrifuging the emulsion to obtain a precipitate, and washing the precipitate; (4) placing the washed precipitate product in an oven and drying it at a constant temperature of 30-150° C. for 0.1-24 hours to obtain the lead tungstate with a micron-branched structure.
